Role of NGOs in military reform in Indonesia - Edwin, Donni (2008)
The role of NGO is crucial in military reform in post Soeharto Indonesia. The significant meaning of NGOs role is connected with high magnitude of constraints and challenges in the military reform process. This paper has assessed two challenges against continuation of military reform namely, there is growing resistance from military and weak political commitment of civilian politicians in promoting democratic civilian control of the military. This paper explores the role of NGOs through their advocacy activities in disseminating ideas in respect of military reform, monitoring implementation of military duty and function, and influencing policy and legislative reform, have played significant role in ensuring the military reform that has not yet been well institutionalized remain to be continued.